A Modified Asphalt Binder Composition and Method of Preparing Thereof - Khairil Azman, Masri; Muzamir, Hasan; Putra Jaya, Ramadhansyah; Mazlan, Abu Seman; Abdul Rahimi, Abdul Rahman (2021)
The present invention provides a modified asphalt binder composition for use in pavement engineering application and construction of high strength expressway and residential area. The modified asphalt binder composition comprising bitumen, nanosilica, nano-titanium dioxide (tio2) particles and metallic fibers. Herein, the bitumen is preferably penetration bitumen grades range from 60 to 70; the nanosilica is preferably colloidal nanosilica and the metallic fibers are preferably steel fibers. The present invention further provides a method of preparing the modified asphalt binder composition comprising the steps of (a) gradually admixing nanosilica to a first pre-heated bitumen to obtain nanosilica modified bitumen; (b) gradually admixing nano-titanium dioxide (tio2) particles to a second pre-heated bitumen to obtain nanotitanium modified bitumen; (c) mixing the nanosilica modified bitumen and the nanotitanium modified bitumen with metallic fibers in a heated mixer having a temperature of 160c to obtain a homogeneous modified asphalt binder composition.